2003
DOI: 10.1046/j.1365-2583.2003.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a G protein‐coupled receptor from the Southern cattle tick Boophilus microplus (Acari: Ixodidae) identifies it as the first arthropod myokinin receptor

Abstract: The myokinins are invertebrate neuropeptides with myotropic and diuretic activity. The lymnokinin receptor from the snail Lymnaea stagnalis (Mollusca) has been the only previously identified myokinin receptor. We had cloned a G protein-coupled receptor (AF228521) from the tick Boophilus microplus (Arthropoda: Acari), 40% identical to the lymnokinin receptor, that we have now expressed in CHO-K1 cells. Myokinins at nanomolar concentrations induced intracellular calcium release, as measured by fluorescent cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 71 publications
2
61
0
Order By: Relevance
“…G, heterotrimeric Gprotein; PLC, phospholipase C; IP3, inositol (1,4,5)-trisphosphate. Data from Yu and Beyenbach, 2002. 3854 snails (Lymnaea stagnalis), cattle ticks (Boophilus microplus) and the fruit fly have a sequence consistent with a G-protein coupled receptor (Radford et al, 2002;Holmes et al, 2003). Furthermore, AlF4 -, a known activator of G-proteins, duplicates the effects of leucokinin in Aedes Malpighian tubules (Yu and Beyenbach, 2001).…”
Section: Transport In Malpighian Tubulesmentioning
confidence: 93%
“…G, heterotrimeric Gprotein; PLC, phospholipase C; IP3, inositol (1,4,5)-trisphosphate. Data from Yu and Beyenbach, 2002. 3854 snails (Lymnaea stagnalis), cattle ticks (Boophilus microplus) and the fruit fly have a sequence consistent with a G-protein coupled receptor (Radford et al, 2002;Holmes et al, 2003). Furthermore, AlF4 -, a known activator of G-proteins, duplicates the effects of leucokinin in Aedes Malpighian tubules (Yu and Beyenbach, 2001).…”
Section: Transport In Malpighian Tubulesmentioning
confidence: 93%
“…The protein sequences of the Lymnaea stagnalis L. (Cox et al, 1997) and Boophilus microplus Canestrini (Holmes et al, 2003) leucokinin-like receptors were also used to confirm the sequence match. The BLOSUM62 matrix (default settings) was used for all BLAST analysis as above.…”
Section: Methodsmentioning
confidence: 99%
“…The protein sequences of the known leucokinin-like receptors, the Drosophila LKR (CG10626; Radford et al, 2002), the lymnokinin receptor (GenBank accession AAD11810; Cox et al, 1997), the B. microplus receptor (AAF72891; Holmes et al, 2003) and the putative A. stephensi receptor (Fig.·3) were aligned using the CLUSTAL X program (Thompson et al, 1994). The sequence alignment was annotated using BioEdit (Hall, 1999) (Fig.·4).…”
Section: Alignment and Comparison Of The Known Leucokinin Receptorsmentioning
confidence: 99%
“…Periviscerokinin was the first conserved neuropeptide identified in ticks by using matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) analysis of single neurons (Neupert et al, 2005). Molecular cloning and functional analysis of the Gprotein-coupled receptor for a kinin-like peptide in the southern cattle tick, Boophilus microplus, further suggested that ticks produce multiple neuropeptides and receptors similar to those identified in other arthropods (Holmes et al, 2000(Holmes et al, , 2003Taneja-Bageshwar et al, 2006). We recently described the complex neuroendocrine network present in the central and peripheral nervous systems of the hard tick, Rhipicephalus appendiculatus, by using 15 different antibodies that recognize various neuropeptides (Šimo et al, 2009).…”
mentioning
confidence: 99%